Evaluating The Effectiveness of Radon Measurement Techniques in Soil Gas: Impact of Hole Depth and Measurement Time - Iqbal, Mochamad; Berlian, Fitra; Al Farishi, Bilal; Ipmawan, Vico Luthfi; Siregar, Rahmat Nawi; Umam, Rofiqul (EKSPLORIUM, 2024)
Radon measurement methodologies are critical for accurate risk assessment and resource optimization, yet challenges persist in determining the optimal sampling depth and measurement duration. These factors significantly influence radon concentration readings, and their impact still needs to be explored in systematic evaluations, particularly in balancing efficiency and accuracy. This study evaluates the effectiveness of radon measurement methodologies by experimenting with how sampling hole depth and measurement duration affect radon concentration in soil gas. Radon experiments were conducted at depths of 0.5 m, 1.0 m, and 1.2 m over a 39-day period in soft tuff rock formations at Institut Teknologi Sumatera. Measurements were taken on Days 0, 6, 12, 18, 27, and 39 using the RAD7 Radon Detector, with multiple cycles to ensure stability. The results indicate that radon concentrations varied significantly with both depth and time, with the highest concentrations observed at 1.2 m on Day 18 (1,089 Bq/m³). A noticeable “lag effect” was observed following rainfall events, where radon levels initially decreased due to soil saturation but spiked as the soil dried. The depth of 0.5 m provided the most consistent measurements, with the lowest coefficient of variation (CV = 31%), making it the most reliable and practical depth for routine radon assessments. Overall, this study highlights the importance of considering environmental conditions, such as rainfall and soil moisture, when interpreting radon data and provides insights into optimizing radon measurement practices for accuracy and efficiency.